Association of ADAMDEC1 haplotype with high factor VIII levels in venous thromboembolism - Berger, Mario; Moscatelli, Henriette; Kulle, Bettina; Luxembourg, Beate; Blouin, Katja; Spannagl, Michael; Lindhoff-Last, Edelgard; Schambeck, Christian M. (Thrombosis and Haemostasis, 2008)
A suggestive locus on chromosome 8 could be shown to be associated with familial high factor VIII (FVIII) levels in venous thromboembolism. The ADAMDEC 1 gene is a candidate expressing an ectodomain sheddase. However, the ectodomain of the clearance receptor for FVIII, the low-density lipoprotein receptor-related protein (LRP), is subject to proteolysis by metalloproteases like ADAMDEC1. Other LRP-interacting proteins are lipoprotein lipase (LPL) and t-PA. For an association study, 165 thrombotic patients with high FVIII levels (from the MAISTHRO, i.e. Main-Isar-thrombosis register) were included. All patients with known causes for high FVIII levels had been previously excluded. The patients were compared with 214 healthy blood donors. Polymorphisms with usually a minor allele frequency > 5 %, i.e. 24 SNPs and two insertion/deletion polymorphisms of LPL gene, eight SNPs of the t-PA gene, and five SNPs of the ADAMDEC1 gene, were analyzed. Haplotype differences were calculated using PHASE. A new polymorphism in intron 7 of the t-PA gene with a minor allele frequency of 2.2% was identified. Analysis of each SNP by the Cochrane-Armitage trend test did not show any significant association between genotype and disease status. Interestingly, the ADAMDEC1 haplotype (rs12674766, rs10087305, rs2291577, rs2291578, rs3765124) differed between cases and controls (p=0.04). In particular, the TGTGG haplotype showed a difference. In conclusion, the ADAMDEC 1 haplotype may indicate an underlying mechanism for high FVIII levels. The only moderate linkage disequilibrium may be due to a possible causal polymorphism in distant introns or the promoter region against a polygenic background.
Keywords: Factor VIII; inherited thrombophilia; metalloprotease; venous thromboembolism